2006
DOI: 10.1097/01.jnen.0000240463.87886.9a
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression and Activity of Neprilysin in Alzheimer Disease Are Associated With Cerebral Amyloid Angiopathy

Abstract: Neprilysin (NEP) degrades amyloid-beta (Abeta) and is thought to contribute to its clearance from the brain. In Alzheimer disease (AD), downregulation of NEP has been suggested to contribute to the development of cerebral amyloid angiopathy (CAA). We examined the relationship among NEP, CAA, and APOE status in AD and elderly control cases. NEP was most abundant in the tunica media of cerebrocortical blood vessels and in pyramidal neurons. In homogenates of the frontal cortex, NEP protein levels were reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 65 publications
7
134
1
Order By: Relevance
“…Neprilysin (NEP), a zincdependent metallopeptidase, serves as the major physiological Aβ-degrading enzyme (9). However, both the expression and activity of NEP decrease with age in AD brains (13,33), and the transcriptional regulatory mechanisms that regulate NEP expression are relatively unknown. In the present study, we observed the DNA methylation status of NEP gene in wild-type N2a cells (N2a/wt), which is devoid of NEP (34), and N2a cells stably expressing human Swedish mutant APP (N2a/APPswe) associated with familial early onset AD (27).…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With mentioning
confidence: 99%
“…Neprilysin (NEP), a zincdependent metallopeptidase, serves as the major physiological Aβ-degrading enzyme (9). However, both the expression and activity of NEP decrease with age in AD brains (13,33), and the transcriptional regulatory mechanisms that regulate NEP expression are relatively unknown. In the present study, we observed the DNA methylation status of NEP gene in wild-type N2a cells (N2a/wt), which is devoid of NEP (34), and N2a cells stably expressing human Swedish mutant APP (N2a/APPswe) associated with familial early onset AD (27).…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With mentioning
confidence: 99%
“…49 Although it is unknown whether the observed age-associated reduction in NEP brain levels occurs by this mechanism, it is known that NEP mRNA and protein levels are, in fact, decreased in the brains, cerebral vasculature, and cerebrospinal fluid of LOAD patients. 19,21,33,50,51 Importantly, it has also been shown that the levels of cortical NEP and vascular NEP in AD brain are inversely related to the levels of insoluble A␤ 48 and the severity of CAA, 33,52 respectively. Because brains with severe CAA had similar reductions in NEP in A␤-free and A␤-laden vessels, it seemed that the decrease in NEP was not simply secondary to CAA, suggesting that low NEP levels may have led to the vascular amyloid deposition.…”
Section: Defects In A␤ Clearance Could Be Causative Of Some Cases Of mentioning
confidence: 99%
“…For example, decreased expression of insulin degrading enzyme (IDE) or neprilysin -both of which are known to degrade Aβ-leads to increased accumulation of Aβ, and ultimately to AD. In contrast, overexpression of these enzymes reduces Aβ levels and attenuates Aβ-related memory deficit [16][17][18][19][20] . Together, these studies provide a compelling case for the role of Aβ aggregation in the pathogenesis of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%